Soil carbon and nitrogen stocks due to land use change in coffee areas at minas gerais state - Cerri, Carlos Clemente; Moreira, Cindy Silva; Alves, Priscila Aparecida; Toledo, Fernando Henrique Ribeiro Barrozo; Castigioni, Bruno de Almeida; Rodrigues, Gabriel Augusto de Andrade; Cerri, Domingos Guilherme Pellegrino; Cerri, Carlos Eduardo Pellegrino; Teixeira, Aldir Alves; Candiano, Cesar Augusto C.; Reis, Marcio Roberto; D’Alessandro, Sergio Cotrim; et al. (Coffee Science - ISSN 1984-3909, 2017)
The type of previous land use to the coffee cultivation and the adopted management practices of coffee pruning may affect the dynamics of soil carbon (C) and nitrogen (N). Thus, the aim of this study was to quantify soil C and N stocks in the three main coffee production regions of Minas Gerais State, evaluating different management systems and coffee cultivation time compared to cultivated pastures. For the calculation of C and N stocks, soil samples were collected to determine the content of C and N, in addition to soil density at different depths. Evaluated situations included management of coffee areas with and without pruning, and the type of previous land use to the coffee crop currently in the areas (i.e. pasture or coffee). The results indicated that coffee cultivation under grazing areas along with the adoption of good agricultural practices such as proper management of pruning and good weed control led to the maintenance of soil C and N stocks over time. Through this fact, it is possible to state that coffee cultivation positively affects soil health.